A medical solid waste-based polymer material and its preparation method and application

By disinfecting and interfacial modification of medical waste, and combining the use of specific raw materials, a medical solid waste base polymer material with excellent mechanical properties is prepared, which solves the problems of waste of medical waste resources and environmental pollution, and realizes the recycling and performance improvement of materials.

CN119504163BActive Publication Date: 2025-04-29SHIJIAZHUANG TIEDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510065515.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The prior art cannot effectively recycle fibers from medical waste, resulting in waste of resources and environmental pollution.

Method used

By disinfecting hypochlorous acid solution and modifying the bandage and infusion device, combined with the use of iron tailings slag, ceramic slag and reinforcement, a medical solid waste base polymer material with excellent mechanical properties was prepared.

Benefits of technology

The recycling of medical waste is realized, the mechanical properties and durability of the materials are improved, and the manufacturing cost and environmental pollution are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504163B_ABST
    Figure CN119504163B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and specifically discloses a medical solid waste-based polymer material, a preparation method thereof, and an application thereof. The medical solid waste-based polymer material comprises: an interface-modified bandage, an ultraviolet radiation-modified infusion set, iron tailings slag, ceramic slag, an alkali-excited solution, and an enhancer. The bandage is soaked and disinfected with a hypochlorous acid solution. Hypochlorous acid can kill pathogenic microorganisms, and the generated chloride ions can also change the osmotic pressure of bacteria and virions, thereby inactivating their cells; the interface of the sterilized bandage is adjusted to improve the adhesion between the bandage fiber and the matrix; the infusion set is subjected to ultraviolet radiation, which can increase the roughness of the surface of the infusion set while disinfecting and sterilizing, improve the adhesion between the interface of the infusion set and the matrix, and enable the infusion set to be better integrated into the matrix. The present invention realizes the recycling of medical solid waste, and the medical solid waste-based polymer material has excellent mechanical properties. Using it in prefabricated building materials has certain environmental benefits and use value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a medical solid waste-based polymer material and a preparation method and application thereof. Background Art

[0002] Bandages and infusion sets are medical wastes, and their improper disposal may cause problems such as disease transmission and environmental pollution. At present, the treatment methods for medical wastes such as bandages and infusion sets include sanitary landfill, high-temperature incineration and pyrolysis. The sanitary landfill method is to bury medical waste underground and decompose it into harmless substances through the long-term decomposition of microorganisms. It has a large processing capacity, but it requires scientific site selection and anti-seepage measures to prevent toxic substances, pathogens or radioactive substances from infiltrating into the soil with rainwater, and then endangering human health through the food chain. The high-temperature incineration method is to dry, ignite and burn medical waste through the high-temperature flame of the incinerator, and finally convert it into residues and gases. It can effectively destroy the infectious sources and harmful substances in medical wastes, but the smoke and residues emitted will pollute the environment and need to be disposed of harmlessly. The pyrolysis method is to heat and distill the organic matter in medical waste under anaerobic or anoxic conditions, causing it to undergo thermal cracking to form various gases, liquids and solids, from which fuel oil, grease and fuel gas can be extracted. However, it consumes a lot of energy and the treatment of inorganic matter is still imperfect.

[0003] The production of fibers in infusion sets and bandages belongs to the field of fine chemicals and consumes considerable resources and energy. If medical waste can be recycled, it can not only reduce the cost of medical waste treatment, but also further reduce environmental pollution, which has certain environmental benefits and use value. Summary of the invention

[0004] In view of the above problems, the present invention provides a medical solid waste-based polymer material and a preparation method and application thereof. Through the design of various raw materials, the recycling of medical solid waste is achieved, and the medical solid waste-based polymer material has excellent mechanical properties.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] In a first aspect, the present invention provides a medical solid waste-based polymer material, comprising the following raw materials: an interface-modified bandage, an ultraviolet radiation-modified infusion set, iron tailings slag, ceramic slag, an alkali-activated solution, and a strengthening agent;

[0007] The preparation method of the interface modified bandage comprises the following steps:

[0008] Put the bandage into the hypochlorous acid solution, soak it for the first time, and dry it to obtain a sterilized bandage;

[0009] The sterilized bandage is placed in an interface regulator and soaked for a second time to obtain an interface modified bandage.

[0010] Compared with the prior art, the medical solid waste-based polymer material provided by the present invention, the interface modified bandage can hinder the expansion of cracks caused by various effects on the matrix (i.e., gel material), enhance the ductility and toughness of the polymer material, improve the bending strength, tensile strength, shear strength and fatigue strength of the polymer material, and improve the frost resistance and cavitation resistance of the polymer; the ultraviolet radiation modified infusion set can improve the elasticity, ductility, crack resistance and impermeability of the polymer material, and can also improve the thermal insulation performance of the polymer material, and play a role in noise reduction and vibration reduction; iron tailings slag and ceramic slag are rich in silicon and aluminum, and can be used as gelling materials after activation by alkali-activated solution; the addition of a strengthening agent can further ensure the compressive strength of the polymer material, improve the density of the matrix, strengthen the interface area between the bandage fiber and the matrix, improve the early strength and mechanical properties of the polymer material, and can also improve the ability to resist the invasion of harmful substances, thereby improving durability.

[0011] The existing technologies (sanitary landfill method, high temperature incineration method and pyrolysis method) cannot recycle the fibers in the infusion set and bandage materials. The medical solid waste-based polymer material provided by the present invention can make full use of the infusion set and bandage materials to realize the resource utilization of medical solid waste. The present invention uses hypochlorous acid solution to soak and disinfect the bandage. Hypochlorous acid can not only act on the cell wall of bacteria and the shell of viruses on the bandage, but also penetrate into the bacteria and virus bodies, and react with organic polymers such as proteins, nucleic acids and enzymes of the bacteria and virus bodies to kill pathogenic microorganisms; at the same time, the chloride ions produced by hypochlorous acid can also significantly change the osmotic pressure of bacteria and virus bodies, causing their cells to lose activity and die, and thus will not cause the spread of diseases; then the sterilized bandage is subjected to interface adjustment, which can effectively improve the adhesion between the bandage fiber and the matrix, thereby improving the mechanical properties of the geopolymer material and realizing the resource utilization of the bandage. The present invention subjects the infusion set to ultraviolet radiation, which can effectively increase the roughness of the surface of the infusion set while disinfecting and sterilizing, improve the adhesion between the infusion set and the substrate interface, and enable the infusion set to be better integrated into the substrate, thereby realizing resource utilization of the infusion set.

[0012] Preferably, the medical solid waste-based polymer material includes the following raw materials in parts by mass: 5 to 10 parts of interface modified bandage, 5 to 10 parts of ultraviolet radiation modified infusion set, 25 to 40 parts of iron tailings slag, 20 to 35 parts of ceramic slag, 10 to 30 parts of alkali-excited solution and 8 to 15 parts of enhancer.

[0013] The present invention uses the raw materials and their proportions of the medical solid waste-based polymer material to exert the synergistic effect of each raw material, and obtains a medical solid waste-based polymer material with excellent mechanical properties. In addition, the medical solid waste-based polymer material provided by the present invention can be recycled, and after secondary recycling, its compressive strength can be maintained at more than 88%, further reducing the manufacturing cost, saving resources and energy, and using it in prefabricated building materials, which has certain environmental benefits and use value.

[0014] Preferably, the bandage includes at least one of a glass fiber polymer bandage or a polyester fiber polymer bandage.

[0015] Preferably, the effective chlorine concentration of the hypochlorous acid solution is 6wt%~10wt%.

[0016] Preferably, the first soaking time is 30 min to 50 min.

[0017] The present invention does not limit the usage ratio of the bandage to the hypochlorous acid solution, and the hypochlorous acid solution can immerse the bandage. The bandage is immersed in a hypochlorous acid solution of a specific concentration to achieve a sterilization rate of 99.99%; during the first immersion process, the hypochlorous acid solution can also effectively eliminate attachments on the surface of the bandage.

[0018] Preferably, the drying is carried out under a carbon dioxide atmosphere.

[0019] Preferably, the drying temperature is below 60°C, more preferably 10°C to 50°C.

[0020] Carbon dioxide is an alkaline gas with low cost. The present invention adopts carbon dioxide low-temperature drying to effectively eliminate the residual acid on the bandage after being disinfected with the hypochlorous acid solution. At the same time, the bandage is an organic fiber and is easily damaged if the drying temperature is too high. The present invention does not specifically limit the drying time, and the bandage disinfected with the hypochlorous acid solution can be dried.

[0021] For example, after drying, the process further includes breaking the sterile bandage into pieces so that the length of the sterile bandage is 2 mm to 6 mm.

[0022] Preferably, the interface regulator includes at least one of mineral oil, a strong acid solution or a strong oxidant solution.

[0023] Further preferably, the mineral oil includes at least one of white oil, cycloparaffinic oil or aromatic oil.

[0024] Further preferably, the strong acid solution includes at least one of nitric acid solution, perchloric acid solution, hydroiodic acid solution, hydrobromic acid solution, hydrochloric acid solution or sulfuric acid solution.

[0025] Further preferably, the mass concentration of the strong acid solution is 25% to 70%.

[0026] For example, the mass concentration of nitric acid solution is 35%~68%, the mass concentration of perchloric acid solution is 50%~70%, the mass concentration of hydroiodic acid solution is 50%~60%, the mass concentration of hydrobromic acid solution is 50%~60%, the mass concentration of hydrochloric acid solution is 25%~35%, and the mass concentration of sulfuric acid solution is 40%~50%.

[0027] Further preferably, the strong oxidant solution includes at least one of a potassium chlorate solution or a hydrogen peroxide solution.

[0028] Further preferably, the mass concentration of the strong oxidant solution is 8% to 30%.

[0029] For example, the mass concentration of potassium chlorate solution is 8%~12%, and the mass concentration of hydrogen peroxide solution is 20%~30%.

[0030] The present invention can select a suitable interface regulator according to the material of the bandage fiber and the desired adhesion between the bandage fiber and the matrix. Mineral oil can weaken the performance of the interface between the bandage fiber and the matrix, so that when the medical solid waste-based polymer material is damaged and broken, the bandage fiber is easy to slide out, forming evenly distributed fine cracks; while the strong acid solution or strong oxidant solution can strengthen the performance of the interface between the bandage fiber and the matrix, so that when the medical solid waste-based polymer material is damaged and broken, the bandage fiber is not easy to slide out, thereby forming large cracks. In addition, the strong acid solution or the strong oxidant solution has a strong disinfecting effect on pathogens, which can further kill bacteria and viruses on the bandage and inhibit the spread of the disease. The present invention can prepare a high-ductility material with an ultimate tensile strain range of 1% to 5% by adjusting the mechanical properties of the interface between the bandage fiber and the matrix.

[0031] Preferably, the second soaking time is 20 min to 40 min.

[0032] The present invention does not impose any particular limitation on the amount of the sterile bandage and the interface regulator, and the interface regulator can just immerse the sterile bandage.

[0033] For example, after the second soaking is completed, drying is also included.

[0034] Preferably, the length of the interface modified bandage is 2 mm to 6 mm.

[0035] The specific length of the interface-modified bandage can better play the role of the bandage fibers, thereby further improving the ductility and tensile strength of the geopolymer material.

[0036] Preferably, the method for preparing the ultraviolet radiation modified infusion set comprises the following steps:

[0037] The infusion set without the needle is subjected to ultraviolet radiation to obtain an ultraviolet radiation modified infusion set.

[0038] Further preferably, the material of the infusion set includes at least one of polyvinyl chloride, ultra-low density polyethylene, polyolefin elastomer or polyurethane.

[0039] Further preferably, the natural stacking thickness of the infusion set is ≤20 cm.

[0040] Further preferably, the power density of the ultraviolet radiation is 3W / m 2 ~4W / m 2 , the radiation time is 0.5h~1h.

[0041] Under specific ultraviolet radiation conditions, the surface of the infusion set becomes brittle and the smooth surface becomes rough, which increases the adhesion between the infusion set and the substrate. Through interface adjustment, the infusion set material can be better integrated into the substrate and thus play its role. At the same time, ultraviolet radiation under specific conditions can better kill bacteria and viruses on the surface of the infusion set and will not cause the spread of disease.

[0042] For example, after the ultraviolet radiation ends, it also includes fragmentation.

[0043] Preferably, the particle size of the ultraviolet radiation modified infusion set is 0.2 mm to 2 mm.

[0044] Preferably, the iron tailings include the following chemical components in percentage by mass: silicon dioxide 60% to 80%, aluminum oxide 1% to 20%, iron oxide ≤15% and calcium oxide ≤15%.

[0045] Preferably, the specific surface area of ​​the iron tailings is ≥400m 2 / kg, more preferably 410m 2 / kg~480m 2 / kg.

[0046] Preferably, the ceramic slag comprises the following chemical components in percentage by mass: 60% to 80% silicon dioxide, 12% to 20% aluminum oxide, 1% to 15% calcium oxide, ≤2% magnesium oxide and ≤3% iron oxide.

[0047] Preferably, the specific surface area of ​​the ceramic slag is ≥400m 2 / kg, more preferably 410m 2 / kg~480m 2 / kg.

[0048] Preferably, the alkaline exciting solution includes at least one of a water glass solution, a sodium hydroxide solution or a sodium carbonate solution.

[0049] Preferably, the solid content of the alkali-activated solution is 30% to 45%.

[0050] Further preferably, the modulus of the water glass is 1.5-3.0.

[0051] Preferably, the reinforcing agent includes at least one of ultrafine slag powder, silica fume, and fly ash microbeads.

[0052] Preferably, the particle size of the reinforcing agent is 1 μm to 30 μm.

[0053] The specific reinforcing agent of the present invention has excellent volcanic ash activity, and can further enhance the gelling activity of iron tailings slag and ceramic slag, thereby increasing the mechanical properties of the geopolymer material, especially the compressive strength and early strength.

[0054] Preferably, the medical solid waste-based polymer material is prepared by mixing various raw materials and then subjecting them to microwave activation.

[0055] The present invention uses microwaves to activate the mixture of various raw materials, and achieves uniform heating through the interaction between the electromagnetic field and the internal molecules of each raw material, avoiding the local overheating or overcooling caused by uneven traditional heat conduction; microwaves can penetrate into the interior of each raw material, so that the molecules inside the raw material are polarized and move rapidly at the same time, generating heat, achieving simultaneous heating inside and outside, fast heating speed, low energy loss, and high thermal efficiency. In addition, microwaves also have the function of disinfection and sterilization, and can realize the function of re-disinfection and sterilization of infusion sets and bandages, ensuring the effective inactivation of pathogens.

[0056] In a second aspect, the present invention provides a method for preparing the medical solid waste-based polymer material, comprising the following steps:

[0057] The raw materials are weighed according to the mass ratio, mixed, and then subjected to first pressing, microwave activation, second pressing and curing in sequence to obtain a medical solid waste-based polymer material.

[0058] High-temperature steam curing is currently a commonly used accelerated curing method, but it is inefficient (generally requires 2d~7d) and consumes a lot of energy. The present invention uses microwave activation technology to stimulate the performance of the gelling material, which is conducive to the rapid curing and molding of the mixture in the later stage, greatly improving the early strength and final strength, and has high efficiency (within 30min). Since part of the water evaporates to form bubbles during the microwave activation process, a second pressing is required to remove the tiny bubbles in the mixture; finally, the medical solid waste base polymer material is obtained through curing.

[0059] Preferably, the first pressing pressure is 5 MPa to 25 MPa, and the first pressing time is 5 min to 20 min.

[0060] Preferably, the power density of the microwave activation is 0.3 W / cm 3 ~0.45W / cm 3 , activation time is 10min~20min.

[0061] The present invention has found through a large number of experiments that if the power (density) of microwave activation is too low, the required activation time is too long; if the power (density) of microwave activation is too high, it will cause the temperature inside the material to rise seriously, and even generate a large amount of steam, causing the material to collapse.

[0062] Preferably, the second pressing pressure is 5 MPa to 10 MPa, and the second pressing time is 5 min to 10 min.

[0063] Preferably, the curing temperature is 10°C to 35°C, and the curing time is 40h to 60h.

[0064] For example, the curing can be carried out by surface covering curing, which can be carried out indoors or in a curing box with high humidity (RH ≥ 90%) to prevent a large amount of water evaporation from affecting the forming of the geopolymer material.

[0065] Preferably, after the curing is completed, the obtained curing material is placed in an organic silicon solution and subjected to vacuum waterproofing treatment to obtain the medical solid waste-based polymer material.

[0066] Further preferably, the organic silicon solution includes at least one of a silane solution, a silicone resin solution or a silicone emulsion.

[0067] More preferably, the silane solution comprises an isooctyltriethoxysilane solution with a mass concentration of ≥80% or an isobutyltriethoxysilane solution with a mass concentration of ≥98%.

[0068] More preferably, the mass concentration of the silicone resin solution is 30% to 40%.

[0069] More preferably, the mass concentration of the silicone emulsion is 40% to 50%.

[0070] The present invention does not impose any special restrictions on the amount of organic silicon solution used, as long as it can immerse the curing material. Silicone emulsion is a water-in-oil type emulsion, that is, water is the continuous phase and silicone oil is the discontinuous phase. The commonly used base material of silicone emulsion is active ethyl siloxane, and emulsifiers, stabilizers, buffers and additives are added to make it.

[0071] Further preferably, the pressure of the vacuum waterproofing treatment is -70 kPa to -60 kPa, and the pressure is maintained for 1 min to 5 min.

[0072] The present invention can block the pores on the surface of the curing material by controlling various conditions of the vacuum waterproofing treatment, significantly reduce the water absorption rate and permeability of the geopolymer material, help prevent the infiltration of harmful substances such as moisture, salt, and chemicals, reduce the leakage problem of the geopolymer material, and thus protect the steel bars inside the geopolymer material from corrosion.

[0073] In a third aspect, the present invention provides an application of the medical solid waste-based polymer material in prefabricated components.

[0074] Preferably, the thickness of the prefabricated component is 2 cm to 5 cm.

[0075] Preferably, the prefabricated components include industrial plant roof panels, pavement bricks or permanent formwork.

[0076] Existing industrial plant roof panels mainly use color steel plates or reinforced polymers, and permanent formwork usually uses steel formwork or wooden formwork. Compared with steel, the medical solid waste base polymer material provided by the present invention is light and not easy to rust. Compared with wood, the medical solid waste base polymer material provided by the present invention is not easy to crack or deform, and can effectively adapt to the environment of wind and sun. The medical solid waste base polymer material provided by the present invention is used for pavement bricks (such as square bricks or sidewalk bricks). Because the medical solid waste base polymer material has a certain elasticity, it is more comfortable to touch than the harder cement asphalt pavement, and pedestrians are not easy to feel tired.

[0077] In a fourth aspect, the present invention provides a method for recycling the medical solid waste-based polymer material, comprising the following steps:

[0078] The medical solid waste-based geopolymer material is crushed, an alkaline activator is added, and the obtained mixed material is subjected to a first pressing, microwave activation, a second pressing and curing in sequence to obtain a secondary circulation geopolymer material.

[0079] Preferably, the particle size of the crushed medical solid waste-based polymer material is 10 μm to 60 μm, and more preferably 20 μm to 50 μm.

[0080] Preferably, the mass ratio of the medical solid waste-based polymer material to the alkaline activator is 10:(2~3).

[0081] Preferably, the alkaline exciting solution comprises at least one of water glass, sodium hydroxide or sodium carbonate.

[0082] Preferably, the solid content of the alkali-activated solution is 30% to 45%.

[0083] Further preferably, the modulus of the water glass is 2.2-3.3.

[0084] Preferably, the first pressing pressure is 5 MPa to 25 MPa, and the first pressing time is 5 min to 20 min.

[0085] Preferably, the power density of the microwave activation is 0.3 W / cm 3 ~0.45W / cm 3 , activation time is 10min~20min.

[0086] Preferably, the second pressing pressure is 5 MPa to 10 MPa, and the second pressing time is 5 min to 10 min.

[0087] Preferably, the curing temperature is 10°C to 35°C, and the curing time is 40h to 60h. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] Figure 1 This is a SEM image of fly ash microbeads in an embodiment of the present invention;

[0089] Figure 2 This is a SEM image of the curing material in Example 1 of the present invention;

[0090] Figure 3 The particle size distribution diagram of the steel slag in Comparative Example 7 of the present invention;

[0091] Figure 4 This is a fiber morphology diagram on the broken surface when the medical solid waste base polymer material is broken in Application Example 1 of the present invention;

[0092] Figure 5 This is a particle size distribution diagram of the medical solid waste-based polymer material after crushing in Application Example 1 of the present invention;

[0093] Figure 6 This is a morphological diagram of the failure surface when the secondary recycling geopolymer material of Application Example 1 is crushed in the verification test of the present invention. DETAILED DESCRIPTION

[0094] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0095] In the embodiment of the present invention, the silicone resin solution is the "Huantong R" silicone breathable transparent protective coating that meets the international standard ISO 7783-2:2001 and is produced by Chongqing Huantong Construction Engineering Co., Ltd.; the silicone emulsion is the FS-150 silicone waterproofing agent produced by Guangdong Nanxiong Dingcheng New Materials Technology Co., Ltd.

[0096] Unless otherwise specified, the raw materials, reagents, etc. used in the examples of the present invention were obtained through commercial channels.

[0097] The chemical composition and percentage of the reinforcing agent used in the embodiment of the present invention are shown in Table 1. The fly ash microspheres were scanned by electron microscope, and the results are as follows: Figure 1 shown.

[0098] Table 1 Chemical composition and mass content of enhancers (%)

[0099]

[0100] In order to better illustrate the present invention, further examples are given below.

[0101] Example 1

[0102] The present embodiment provides a medical solid waste-based polymer material, which is composed of the following raw materials in parts by mass: 5 parts of interface modified bandage, 6 parts of ultraviolet radiation modified infusion set, 25 parts of iron tailings slag, 28 parts of ceramic slag, 28 parts of alkali-activated solution (water glass solution with a solid content of 34% and a modulus of 2.5) and 8 parts of a strengthening agent (silica fume with an average particle size of 10 μm).

[0103] The iron tailings include the following chemical components by mass percentage: silicon dioxide 75.60%, aluminum oxide 3.12%, iron oxide 13.51%, calcium oxide 3.41%, magnesium oxide 1.71% and manganese oxide 0.16%; the specific surface area of ​​the iron tailings is 450m 2 / kg. The ceramic slag includes the following chemical components by mass percentage: 70.51% silicon dioxide, 19.50% aluminum oxide, 1.38% calcium oxide, 1.04% magnesium oxide and 2.11% iron oxide; the specific surface area of ​​the ceramic slag is 445m 2 / kg.

[0104] The method for preparing the above-mentioned medical solid waste-based polymer material comprises the following steps:

[0105] S1, Preparation of interface modified bandage:

[0106] Put the polyester fiber polymer bandage into a hypochlorous acid solution with an effective chlorine concentration of 8wt%, soak it for 30 minutes, dry it at room temperature in a concrete carbonization test box (about 3 minutes), and cut it to obtain a 5mm long sterilized bandage;

[0107] The sterilized bandage was placed in white oil, immersed for a second time for 30 minutes, and then dried to obtain an interface-modified bandage with a length of 5 mm.

[0108] S2, Preparation of UV-radiation-modified infusion set:

[0109] The polyvinyl chloride infusion set without the needle was irradiated with UV for 1 hour. The natural stacking thickness of the infusion set was 17 cm and the power density of the UV radiation was 3.5 W / m 2 , sheared to obtain an ultraviolet radiation modified infusion set with a particle size of 1 mm.

[0110] It should be noted that there is no limitation on the order between S1 and S2.

[0111] S3, weigh the raw materials according to the mass ratio, mix the raw materials, put them into the plastic mold, and perform the first pressing at 15MPa for 10min to obtain a test block with a side length of 70.7mm; 3 After microwave activation for 15 minutes (six test pieces were placed in a 20L microwave oven at the same time, the heating power of the microwave oven was 800W), the second pressing was performed at 8MPa pressure for 7 minutes, and then the surface was coated and cured for 48 hours at room temperature to obtain the cured material. The cured material was scanned by electron microscope, and the results were as follows Figure 2 shown.

[0112] S4, placing the curing material into 85wt% isooctyltriethoxysilane solution, performing vacuum waterproofing treatment at a pressure of -65kPa, maintaining the pressure for 3 minutes, and obtaining the medical solid waste-based polymer material.

[0113] Example 2

[0114] The present embodiment provides a medical solid waste-based polymer material, which is composed of the following raw materials in parts by mass: 10 parts of an interface-modified bandage, 5 parts of an ultraviolet radiation-modified infusion set, 32 parts of iron ore tailings slag, 35 parts of ceramic slag, 25 parts of an alkali-activated solution (a sodium hydroxide solution with a solid content of 40%), and 12 parts of a strengthening agent (ultrafine slag powder with an average particle size of 20 μm).

[0115] The iron tailings include the following chemical components by mass percentage: 60.87% silicon dioxide, 18.26% aluminum oxide, 12.15% iron oxide and 5.11% calcium oxide; the specific surface area of ​​the iron tailings is 413m 2 / kg. The ceramic slag includes the following chemical components by mass percentage: 77.59% silicon dioxide, 12.88% aluminum oxide, 5.03% calcium oxide, 0.98% magnesium oxide and 1.34% iron oxide; the specific surface area of ​​the ceramic slag is 470m 2 / kg.

[0116] The method for preparing the above-mentioned medical solid waste-based polymer material comprises the following steps:

[0117] S1, Preparation of interface modified bandage:

[0118] Put the glass fiber polymer bandage into a hypochlorous acid solution with an effective chlorine concentration of , soak for 50 minutes, dry it at room temperature in a concrete carbonization test box (about 4 minutes), and cut it to obtain a 2mm long sterilized bandage;

[0119] The sterilized bandage was placed in a 50 wt % nitric acid solution, immersed for a second time for 25 minutes, and then dried to obtain a 2 mm long interface modified bandage.

[0120] S2, Preparation of UV-radiation-modified infusion set:

[0121] The ultra-low density polyethylene infusion set without the needle was irradiated with UV for 0.8 hours. The natural stacking thickness of the infusion set was 10 cm and the power density of the UV radiation was 3 W / m 2 , sheared to obtain an ultraviolet radiation modified infusion set with a particle size of 0.2 mm.

[0122] It should be noted that there is no limitation on the order between S1 and S2.

[0123] S3, weigh each raw material according to the mass ratio, mix the raw materials, put them into a plastic mold and perform the first pressing at 5MPa for 20min to obtain a test block with a side length of 70.7mm; 3 After microwave activation for 20 minutes (6 test blocks were placed in a microwave oven with a volume of 20L at the same time, and the heating power of the microwave oven was 700W), a second pressing was carried out at a pressure of 5MPa for 10 minutes, and then the surface was coated and cured for 58 hours at room temperature to obtain a cured material.

[0124] S4, placing the curing material into a 98wt% isobutyltriethoxysilane solution, performing vacuum waterproofing treatment at a pressure of -70kPa, maintaining the pressure for 1 minute, and obtaining the medical solid waste-based polymer material.

[0125] Example 3

[0126] The present embodiment provides a medical solid waste-based polymer material, which is composed of the following raw materials in parts by mass: 7 parts of interface modified bandage, 10 parts of ultraviolet radiation modified infusion set, 38 parts of iron tailings slag, 20 parts of ceramic slag, 13 parts of alkali-activated solution (sodium carbonate solution with a solid content of 45%), and 10 parts of a strengthener (fly ash microbeads with an average particle size of 3 μm).

[0127] The iron tailings include the following chemical components by mass percentage: silicon dioxide 77.62%, aluminum oxide 1.94%, iron oxide 5.68% and calcium oxide 11.03%; the specific surface area of ​​the iron tailings is 478m 2 / kg. The ceramic slag includes the following chemical components by mass percentage: 60.98% silicon dioxide, 18.72% aluminum oxide, 13.30% calcium oxide, 1.77% magnesium oxide and 2.10% iron oxide; the specific surface area of ​​the ceramic slag is 415m 2 / kg.

[0128] The method for preparing the above-mentioned medical solid waste-based polymer material comprises the following steps:

[0129] S1, Preparation of interface modified bandage:

[0130] Put the glass fiber polymer bandage into a hypochlorous acid solution with an effective chlorine concentration, soak it for 30 minutes, dry it at room temperature in a concrete carbonization test box (about 3 minutes), and cut it to obtain a 4mm long sterilized bandage;

[0131] The sterilized bandage was placed in a 10 wt % potassium chlorate solution, immersed for a second time for 40 minutes, and then dried to obtain a 4 mm long interface modified bandage.

[0132] S2, Preparation of UV-radiation-modified infusion set:

[0133] The polyolefin elastomer infusion set without the needle was irradiated with UV for 0.5 h. The natural stacking thickness of the infusion set was 15 cm and the power density of the UV radiation was 3.5 W / m 2 , sheared to obtain an ultraviolet radiation modified infusion set with a particle size of 2 mm.

[0134] It should be noted that there is no limitation on the order between S1 and S2.

[0135] S3, weigh each raw material according to the mass ratio, mix each raw material, put it into a plastic mold and perform the first pressing for 5 minutes at 25MPa to obtain a test block with a side length of 70.7mm; 3 After microwave activation for 10 minutes (6 test blocks were placed in a microwave oven with a volume of 20L at the same time, and the heating power of the microwave oven was 900W), a second pressing was carried out at a pressure of 10MPa for 5 minutes, and then the surface was coated and cured for 40 hours at room temperature to obtain a cured material.

[0136] S4, placing the curing material into a 35wt% silicone resin solution, performing vacuum waterproofing treatment at a pressure of -60kPa, maintaining the pressure for 5 minutes, and obtaining the medical solid waste-based polymer material.

[0137] Example 4

[0138] The present embodiment provides a medical solid waste-based polymer material, which is composed of the following raw materials in parts by mass: 8 parts of interface modified bandage, 8 parts of ultraviolet radiation modified infusion set, 40 parts of iron tailings slag, 26 parts of ceramic slag, 25 parts of alkali-activated solution (water glass solution with a solid content of 30% and a modulus of 2.0) and 15 parts of a strengthening agent (silica fume with an average particle size of 10 μm).

[0139] The iron tailings include the following chemical components by mass percentage: 66.42% silicon dioxide, 5.30% aluminum oxide, 10.65% iron oxide and 10.73% calcium oxide; the specific surface area of ​​the iron tailings is 439m 2 / kg. The ceramic slag includes the following chemical components by mass percentage: 68.92% silicon dioxide, 15.46% aluminum oxide, 9.51% calcium oxide, 1.32% magnesium oxide and 2.33% iron oxide; the specific surface area of ​​the ceramic slag is 462m 2 / kg.

[0140] The method for preparing the above-mentioned medical solid waste-based polymer material comprises the following steps:

[0141] S1, Preparation of interface modified bandage:

[0142] The polyester fiber polymer bandage was placed in a hypochlorous acid solution with an effective chlorine concentration of 8 wt%, and after a first soaking for 40 minutes, it was dried at room temperature in a concrete carbonization test box (about 4 minutes), and cut to obtain a 6 mm long sterilized bandage;

[0143] The sterilized bandage was placed in a 45 wt % sulfuric acid solution, immersed for a second time for 30 minutes, and then dried to obtain a 6 mm long interface modified bandage.

[0144] S2, Preparation of UV-radiation-modified infusion set:

[0145] The polyurethane infusion set without the needle was irradiated with UV for 0.7 hours. The natural stacking thickness of the infusion set was 18 cm and the power density of the UV radiation was 4 W / m 2 , sheared to obtain an ultraviolet radiation modified infusion set with a particle size of 1.5 mm.

[0146] It should be noted that there is no limitation on the order between S1 and S2.

[0147] S3, weigh the raw materials according to the mass ratio, mix the raw materials, put them into the plastic mold, and perform the first pressing for 12 minutes at 18MPa to obtain a test block with a side length of 70.7mm; 3After microwave activation for 15 minutes (6 test blocks were placed in a microwave oven with a volume of 20L at the same time, and the heating power of the microwave oven was 800W), a second pressing was carried out at a pressure of 7MPa for 8 minutes, and then the surface was coated and cured at room temperature for 50 hours to obtain a cured material.

[0148] S4, placing the curing material into 45wt% silicone emulsion, performing vacuum waterproofing treatment at a pressure of -65kPa, maintaining the pressure for 4 minutes, and obtaining the medical solid waste-based polymer material.

[0149] Comparative Example 1

[0150] This comparative example provides a medical solid waste-based polymer material, which is similar to Example 1, except that the interface-modified bandage is replaced with a sterilized bandage of the same quality (without interface modification). The remaining raw material components and proportions are the same as those in Example 1 and will not be described in detail.

[0151] The method for preparing the above-mentioned medical solid waste-based polymer material comprises the following steps:

[0152] S1. Preparation of sterile bandage:

[0153] The polyester fiber polymer bandage was placed in a hypochlorous acid solution with an effective chlorine concentration of 8 wt %, and after a first immersion for 30 min, it was dried at room temperature in a concrete carbonization test box (about 3 min) and cut to obtain a 5 mm long sterilized bandage.

[0154] S2~S4 are the same as those in Example 1 and will not be described in detail.

[0155] Comparative Example 2

[0156] This comparative example provides a medical solid waste-based polymer material, which is similar to Example 1, except that the interface-modified bandage is replaced with 5 mm long glass wool of the same mass. The remaining raw material components and proportions are the same as those of Example 1 and will not be described in detail.

[0157] The method for preparing the above-mentioned medical solid waste-based polymer material is similar to that in Example 1, except that step S1 is omitted and will not be described in detail.

[0158] Comparative Example 3

[0159] This comparative example provides a medical solid waste-based polymer material, which is similar to Example 1, except that the ultraviolet radiation modified infusion set is replaced with an unmodified infusion set of the same quality without the needle. The remaining raw material components and proportions are the same as those in Example 1 and will not be repeated.

[0160] The method for preparing the above-mentioned medical solid waste-based polymer material is similar to that in Example 1, except that step S2 is omitted and will not be described in detail.

[0161] Comparative Example 4

[0162] This comparative example provides a medical solid waste-based polymer material, which is similar to Example 1, except that the ultraviolet radiation modified infusion set is replaced with rosin resin of the same mass and particle size of 1 mm. The remaining raw material components and proportions are the same as those in Example 1 and will not be repeated.

[0163] The method for preparing the above-mentioned medical solid waste-based polymer material is similar to that in Example 1, except that step S2 is omitted and will not be described in detail.

[0164] Comparative Example 5

[0165] This comparative example provides a medical solid waste-based polymer material, which is similar to Example 1, except that the silica fume is replaced with an equal mass of iron tailings slag. That is, it is composed of the following raw materials in parts by mass: 5 parts of interface modified bandage, 6 parts of ultraviolet radiation modified infusion set, 33 parts of iron tailings slag, 28 parts of ceramic slag and 28 parts of alkali-activated solution (water glass solution with a solid content of 34% and a modulus of 2.5).

[0166] The preparation method of the above-mentioned medical solid waste-based polymer material is similar to that in Example 1 and will not be repeated herein.

[0167] Comparative Example 6

[0168] This comparative example provides a medical solid waste-based polymer material, which is similar to Example 1, except that the ceramic slag is replaced with sintered clay brick powder of equal mass. The sintered clay brick powder includes the following chemical components in mass percentage: SiO2 61.86%, MgO 2.08%, Na2O 1.61%, Fe2O3 6.51%, CaO 1.45%, Al2O3 21.38% and K2O 3.34%; the specific surface area of ​​the sintered clay brick powder is 460m 2 The remaining raw material components and proportions are the same as those in Example 1 and will not be described in detail.

[0169] The preparation method of the above-mentioned medical solid waste-based polymer material is similar to that in Example 1 and will not be repeated herein.

[0170] Comparative Example 7

[0171] This comparative example provides a medical solid waste-based polymer material, which is similar to Example 1, except that the iron tailings slag is replaced with steel slag of equal mass. The steel slag includes the following chemical components in mass percentage: SiO2 17.66%, MgO 5.86%, Na2O 0.20%, Fe2O3 22.70%, CaO 43.40%, Al2O3 5.61% and K2O 0.21%; the particle size distribution of the steel slag is as follows: Figure 3 The remaining raw material components and proportions are the same as those in Example 1 and will not be described in detail.

[0172] The preparation method of the above-mentioned medical solid waste-based polymer material is similar to that in Example 1 and will not be repeated herein.

[0173] Comparative Example 8

[0174] This comparative example provides a preparation method of a medical solid waste-based polymer material, which is similar to Example 1, except that in S3, microwave activation is replaced by water bath heating. The raw materials and proportions of the medical solid waste-based polymer material are the same as those in Example 1 and are not described in detail.

[0175] The preparation method of medical solid waste-based polymer material specifically comprises the following steps:

[0176] S1~S2 are the same as those in Example 1 and will not be described in detail.

[0177] S3, weigh each raw material according to the mass ratio, mix the raw materials, put them into a plastic mold and perform the first pressing at 15MPa for 10 minutes to obtain a test block with a side length of 70.7mm; activate the test block in a water bath at 80℃ for 30min, perform the second pressing at a pressure of 8MPa for 7min, and then coat the surface with a film and cure for 48h at room temperature to obtain a cured material.

[0178] S4 is the same as in Example 1 and will not be described in detail.

[0179] Comparative Example 9

[0180] This comparative example provides a preparation method of a medical solid waste-based polymer material, which is similar to Example 1, except that in S3, the test block is not subjected to microwave activation and second pressing. The raw materials and proportions of the medical solid waste-based polymer material are the same as those in Example 1 and are not described in detail.

[0181] The preparation method of medical solid waste-based polymer material specifically comprises the following steps:

[0182] S1~S2 are the same as those in Example 1 and will not be described in detail.

[0183] S3, weighing each raw material according to the mass ratio, mixing each raw material, putting it into a plastic mold and performing the first pressing for 10 minutes at 15MPa to obtain a test block with a side length of 70.7mm; curing the surface of the test block at room temperature for 60 hours to obtain a cured material. It was found that the cured material was not cured.

[0184] Application Example 1

[0185] This application example provides a method for recycling polymer materials from medical solid waste, comprising the following steps:

[0186] The medical solid waste-based polymer material of Example 1 is crushed (the fiber morphology on the broken surface of the medical solid waste-based polymer material when it is crushed is shown in FIG. Figure 4 The particle size distribution of the crushed medical solid waste base polymer material can be found in Figure 5 ), the mass of the medical solid waste-based polymer material is 707g, 150g of water glass solution with a solid content of 43% and a modulus of 2.5 is added, the resulting mixture is placed in a plastic mold, and the first pressing is performed at a pressure of 15MPa for 10min, and then at 0.38W / cm 3 The mixture was activated by microwave for 15 min, then pressed for a second time at a pressure of 8 MPa for 7 min, and the surface was coated and cured at room temperature for 48 h to obtain a secondary circulation geopolymer material.

[0187] Application Example 2

[0188] This application example provides a method for recycling polymer materials from medical solid waste, comprising the following steps:

[0189] The medical solid waste-based polymer material of Example 2 was crushed (ground to a maximum particle size of 50 μm), the mass of the medical solid waste-based polymer material was 703 g, 210 g of a water glass solution with a solid content of 32% and a modulus of 3.0 was added, and the resulting mixture was placed in a plastic mold, and the first pressing was performed at a pressure of 6 MPa for 20 min, and then at a pressure of 0.33 W / cm 3 The mixture was activated by microwave for 15 min, and then pressed for a second time at a pressure of 5 MPa for 10 min. The surface was coated and cured at room temperature for 60 h to obtain a secondary circulating geopolymer material.

[0190] Application Example 3

[0191] This application example provides a method for recycling polymer materials from medical solid waste, comprising the following steps:

[0192] The medical solid waste-based polymer material of Example 3 was crushed (ground to a maximum particle size of 50 μm), the mass of the medical solid waste-based polymer material was 705 g, 175 g of a sodium hydroxide solution with a solid content of 40% was added, and the resulting mixture was placed in a plastic mold and pressed for a first time at a pressure of 25 MPa for 5 min, and then at a pressure of 0.42 W / cm 3 After microwave activation for 15 minutes, a second pressing was carried out at a pressure of 10 MPa for 5 minutes, and the surface was coated and cured at room temperature for 50 hours to obtain a secondary circulation geopolymer material.

[0193] Application Comparative Example 1

[0194] This comparative application example provides a recycling method for medical solid waste-based polymer materials, which is similar to Application Example 1, except that the medical solid waste-based polymer materials of Example 1 are replaced with the medical solid waste-based polymer materials of Comparative Example 1. Specifically, the following steps are included:

[0195] The medical solid waste-based polymer material of Comparative Example 1 was crushed (ground to a maximum particle size of 50 μm), the mass of the medical solid waste-based polymer material was 706 g, 150 g of a water glass solution with a solid content of 43% and a modulus of 2.5 was added, and the resulting mixture was placed in a plastic mold, and the first pressing was performed at a pressure of 15 MPa for 10 minutes, and then at a pressure of 0.38 W / cm 3 The mixture was activated by microwave for 15 min, then pressed for a second time at a pressure of 8 MPa for 7 min, and the surface was coated and cured at room temperature for 48 h to obtain a secondary circulation geopolymer material.

[0196] Application Comparative Example 2

[0197] This comparative application example provides a recycling method for medical solid waste-based polymer materials, which is similar to Application Example 1, except that the medical solid waste-based polymer materials of Example 1 are replaced with the medical solid waste-based polymer materials of Comparative Example 2. Specifically, the following steps are included:

[0198] The medical solid waste-based polymer material of Comparative Example 2 was crushed (ground to a maximum particle size of 50 μm), the mass of the medical solid waste-based polymer material was 701 g, 150 g of a water glass solution with a solid content of 43% and a modulus of 2.5 was added, and the resulting mixture was placed in a plastic mold, and the first pressing was performed at a pressure of 15 MPa for 10 minutes, and then at a pressure of 0.38 W / cm 3 The mixture was activated by microwave for 15 min, then pressed for a second time at a pressure of 8 MPa for 7 min, and the surface was coated and cured at room temperature for 48 h to obtain a secondary circulation geopolymer material.

[0199] Application Comparative Example 3

[0200] This comparative application example provides a recycling method for medical solid waste-based polymer materials, which is similar to Application Example 1, except that the medical solid waste-based polymer materials of Example 1 are replaced with the medical solid waste-based polymer materials of Comparative Example 3. Specifically, the following steps are included:

[0201] The medical solid waste-based polymer material of Comparative Example 4 was crushed (ground to a maximum particle size of 50 μm), the mass of the medical solid waste-based polymer material was 698 g, 150 g of a water glass solution with a solid content of 43% and a modulus of 2.5 was added, and the resulting mixture was placed in a plastic mold, and the first pressing was performed at a pressure of 15 MPa for 10 min, and then at a pressure of 0.38 W / cm 3 The mixture was activated by microwave for 15 min, then pressed for a second time at a pressure of 8 MPa for 7 min, and the surface was coated and cured at room temperature for 48 h to obtain a secondary circulation geopolymer material.

[0202] Verification test

[0203] According to the "Standard for Test Methods for Physical and Mechanical Properties of Geopolymers" (GB / T 50081-2019), the geopolymer materials of Examples 1 to 4, Comparative Examples 1 to 8, Application Examples 1 to 3 and Application Comparative Examples 1 to 3 were tested for mechanical properties such as compressive strength, tensile strength, elongation, and waterproofness. The test results are shown in Table 2. The morphology of the secondary recycled geopolymer material of Application Example 1 on the broken surface when it is broken is shown in Table 2. Figure 6 As shown, at this time, the fibers of the infusion set and bandage have been crushed and are not visible to the naked eye.

[0204] Table 2 Mechanical properties test results of geopolymer materials

[0205]

[0206] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A medical solid waste-based polymer material, characterized in that: The raw materials include: interface modified bandage, ultraviolet radiation modified infusion set, iron tailings slag, ceramic slag, alkali excitation solution and strengthening agent; The reinforcing agent includes at least one of ultrafine slag powder, silica ash or fly ash microbeads; The preparation method of the ultraviolet radiation modified infusion set comprises the following steps: The infusion set without the needle is subjected to ultraviolet radiation to obtain an ultraviolet radiation modified infusion set; The material of the infusion set includes at least one of polyvinyl chloride, ultra-low density polyethylene, polyolefin elastomer or polyurethane; the natural stacking thickness of the infusion set is ≤20cm, and the power density of the ultraviolet radiation is 3W / m 2 ~4W / m 2 , the radiation time is 0.5h~1h; the particle size of the ultraviolet radiation modified infusion device is 0.2mm~2mm; The preparation method of the interface modified bandage comprises the following steps: Putting the bandage into the hypochlorous acid solution for a first soaking and drying to obtain a sterilized bandage; the bandage comprises at least one of a glass fiber polymer bandage or a polyester fiber polymer bandage; The sterilized bandage is placed in an interface regulator for a second soaking to obtain an interface modified bandage; the interface regulator includes at least one of mineral oil, a strong acid solution or a strong oxidant solution; and the length of the interface modified bandage is 2 mm to 6 mm.

2. The medical solid waste-based polymer material according to claim 1, characterized in that: The medical solid waste-based polymer material includes the following raw materials in parts by weight: 5 to 10 parts of interface modified bandage, 5 to 10 parts of ultraviolet radiation modified infusion set, 25 to 40 parts of iron tailings slag, 20 to 35 parts of ceramic slag, 10 to 30 parts of alkali-activated solution and 8 to 15 parts of enhancer.

3. The medical solid waste-based polymer material according to claim 1 or 2, characterized in that: The effective chlorine concentration of the hypochlorous acid solution is 6wt%~10wt%; The first soaking time is 30min to 50min; The drying is carried out in a carbon dioxide atmosphere, and the drying temperature is below 60° C.; The second soaking time is 20 min to 40 min.

4. The medical solid waste-based polymer material according to claim 1 or 2, characterized in that: The iron tailings slag includes the following chemical components in percentage by mass: silicon dioxide 60% to 80%, aluminum oxide 1% to 20%, iron oxide ≤ 15% and calcium oxide ≤ 15%; The ceramic slag includes the following chemical components in percentage by mass: 60% to 80% silicon dioxide, 12% to 20% aluminum oxide, 1% to 15% calcium oxide, ≤2% magnesium oxide and ≤3% iron oxide; The alkali-stimulated solution comprises at least one of a water glass solution, a sodium hydroxide solution or a sodium carbonate solution, and the solid content of the alkali-stimulated solution is 30% to 45%.

5. The method for preparing the medical solid waste-based polymer material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials are weighed according to the mass ratio, mixed, and then subjected to first pressing, microwave activation, second pressing and curing in sequence to obtain a medical solid waste-based polymer material.

6. The method for preparing the medical solid waste-based polymer material according to claim 5, characterized in that: The first pressing pressure is 5 MPa to 25 MPa, and the first pressing time is 5 min to 20 min; The power density of the microwave activation was 0.3 W / cm 3 ~0.45W / cm 3 , activation time is 10min~20min; The second pressing pressure is 5MPa~10MPa, and the second pressing time is 5min~10min; The curing temperature is 10°C to 35°C, and the curing time is 40h to 60h.

7. The method for preparing the medical solid waste-based polymer material according to claim 5, characterized in that: After the curing is completed, the obtained curing material is placed in an organic silicon solution and subjected to vacuum waterproofing treatment to obtain the medical solid waste-based polymer material; The organosilicon solution includes at least one of a silane solution, a silicone resin solution or a silicone emulsion; The pressure of the vacuum waterproofing treatment is -70 kPa to -60 kPa, and the pressure is maintained for 1 min to 5 min.

8. Use of the medical solid waste-based polymer material according to any one of claims 1 to 4 in prefabricated components.

9. The use of the medical solid waste-based polymer material in prefabricated components as claimed in claim 8, characterized in that: The thickness of the prefabricated component is 2 cm to 5 cm; The prefabricated components include industrial plant roof panels, pavement bricks or permanent formwork.

10. The method for recycling medical solid waste-based polymer materials according to any one of claims 1 to 4, characterized in that: The following steps are involved: The medical solid waste-based geopolymer material is crushed, an alkaline activator is added, and the obtained mixed material is subjected to first pressing, microwave activation, second pressing and curing in sequence to obtain a secondary circulation geopolymer material; The mass ratio of the medical solid waste-based polymer material to the alkaline activator is 10:(2-3).

Citation Information

Patent Citations

  • Geopolymer unshaped refractory material as well as preparation method and application thereof

    CN118146012A

  • Fly ash-slag based geopolymer cementing material and preparation method thereof

    CN118955027A